On the solution of the Cayley impulsive dynamic control systems - Atta, Gulnaz; Younus, Awais (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
In this article, we state Cayley-type impulsive dynamic control systems on time scales. For such a system, we study a new fundamental matrix and matrix exponential for impulsive dynamic systems (IDS). We get some fundamental properties for the transition matrix for IDS. To illustrate our results, we have included some numerical examples.